2022
DOI: 10.56578/jimd010107
|View full text |Cite
|
Sign up to set email alerts
|

Management of Human Capital Development in the Era of the Digital Economy

Abstract: The purpose of the article is to study the peculiarities of managing the development of human capital in the conditions of digitalization. In the course of the study, the method of measuring the human potential index, developed by the UN - the Human Development Index, including taking into account socio-economic inequality, the Gender Inequality Index and the multidimensional poverty index, was applied as basic indicators that reflect the level of development of human capital, which is especially important in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The interaction between positive affectivity and creative self-efficacy shows that members with higher levels of positive affectivity also have higher perceptions of creative self-efficacy, which makes the effect of creative self-efficacy on creative behaviors stronger to some extent, and members’ creative behaviors more likely to be achieved at this time. Previous studies have mainly considered the moderating effect between creative self-efficacy and members’ creative behaviors from external situational variables, but less from the perspective of affective traits [ 61 , 62 , 63 ]. The results also coincided with Mielniczuk and Laguna [ 64 ] which found that self-efficacy predicts the innovative behavior of entrepreneurs.…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…The interaction between positive affectivity and creative self-efficacy shows that members with higher levels of positive affectivity also have higher perceptions of creative self-efficacy, which makes the effect of creative self-efficacy on creative behaviors stronger to some extent, and members’ creative behaviors more likely to be achieved at this time. Previous studies have mainly considered the moderating effect between creative self-efficacy and members’ creative behaviors from external situational variables, but less from the perspective of affective traits [ 61 , 62 , 63 ]. The results also coincided with Mielniczuk and Laguna [ 64 ] which found that self-efficacy predicts the innovative behavior of entrepreneurs.…”
Section: Discussion and Recommendationmentioning
confidence: 99%
“…It also becomes an important engine to promote growth of foreign trade [55]. Meanwhile, the development of DE has an important impact on human capital [56], promotes transformation and upgrading of human capital [57], and significantly improves the level of human capital structure [58]. The upgrading of human capital structure actively promotes the improvement of regional innovation ability [59], improves the technical level of export products, and promotes the improvement of foreign trade competitiveness.…”
Section: Digital Economymentioning
confidence: 99%
“…At present, the wave of informatization characterized by digitalization, networking and intelligence is prevailing the world, promoting mankind to officially enter the digital information society [1][2][3][4][5][6][7]. The rapid development of information technology has had a major impact on all industries in society, not only changing human production and lifestyle [8][9][10][11][12], but also bringing about major changes in thinking and learning methods, and the new era background and new social background put forward higher goals for the cultivation of innovative talents [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%